Association of Molecular Biomarker Heterogeneity With Treatment Pattern and Disease Outcomes in Multifocal or Multicentric Breast Cancer - Li, Shuai; Wu, Jiayi; Huang, Ou; He, Jianrong; Chen, Weiguo; Li, Yafen; Chen, Xiaosong; Shen, Kunwei (Frontiers in Oncology, 2022)
Abstract Purpose: To evaluate the rates of estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor 2 (HER2), and Ki-67 heterogeneity in multifocal or multicentric breast cancer (MMBC) and its association with treatment pattern and disease outcomes. Methods: MMBC patients with ER, PR, HER2, and Ki67 results for each tumor focus were retrospectively analyzed using Kappa test and categorized into the homogeneous group (Homo group) and the heterogeneous group (Hetero group). Chi-square test were performed to compare the clinical features and treatment options between the groups. Disease-free survival (DFS) and overall survival (OS) rates were estimated from Kaplan-Meier curves and compared between two groups. Results: A total of 387 patients were included and 93 (24.0%) were classified into the Hetero group. Adjuvant endocrine therapy was more frequently assigned for patients in the Hetero group than in the Homo group (84.9% vs. 71.7%, P = 0.046). There was no difference in terms of adjuvant anti-HER2 therapy (28.3% vs. 19.6%, P = 0.196) and chemotherapy (69.9% vs. 69.8%, P = 0.987) usage between two groups. At a median follow-up of 36 months, DFS rates were 81.2% for the Hetero group and 96.5% for the Homo group (P = 0.041, Adjusted HR 2.95, 95% CI 1.04-8.37). The estimated 3-year OS rates for the groups were 95.8% and 99.5%, respectively (P = 0.059, Adjusted HR 5.36, 95% CI 0.97-29.69). Conclusion: Heterogeneity of ER, PR, HER2, or Ki67 was present in 24.0% patients with MMBC. Biomarkers heterogeneity influenced adjuvant endocrine therapy usage and was associated with worse disease outcomes, indicating further clinical evaluation.